Tree bark as a bioindicator of air pollution in Navarra, Spain (Water, Air, & Soil Pollution, 1997)
During a two year research period from 1992 to 1993, samples of different species of trees were taken in 17 forest stands located in Navarra, Spain. From these samples, bark extracts were prepared in which the pH and the conductivity were measured. The health of the sampling trees was also evaluated by determining the degree of defoliation and decoloration of the canopies. The bark tissue analysis revealed the presence of an environmental acidity gradient that decreased from NW to SE. This coincides with the location of important sources of pollution and their course of transport and dispersion. On the other hand, in the samples of Quercus ilex a significant correlation between the pH and the defoliation levels (P<0.01, r = 0.62) was found. This fact reveals the potential usefulness of tree bark as a health bioindicator of trees.

Aboveground litter production and bioelement potential return in an evergreen oak (Quercus rotundifolia) woodland near Salamanca (Spain) (Ann. For. Sci., 1996)
Total aboveground production of trees has been determined in a Quercus rotundifolia evergreen oak woodland developed over a chromic Luvisol. The woodland is located close to the city of Salamanca (central-western Spain). Litter fall occurs throughout the year, with a maximum from April to June owing to leaf fall. Mean litter production is 1.9 Mg ha-1 year-1, although variations from year to year are observed, mostly due to water stress in summer. The mean area of influence of litter fall of each tree is about 4 m outside the crown shadow and the leaf percentage (55%) over the total aboveground litter production shows that the system is mature. Tree inflorescences are found to have the highest concentration in bioelements, although the latter are mostly returned through the leaves (with the exception of K).

MICROMORPHOLOGICAL, PHYSICAL, AND CHEMICAL CHARACTERISTICS OF LEACHING POORLY DRAINED FLAT SOILS OF CENTRAL SPAIN (ARID SOIL RESEARCH AND REHABILITATION, 1995)
The eluviation process has been analyzed in horizons of Luvisols, Cambisols, and Acrisols on rana surfaces and in one Luvisol from the uppermost terraces of the Henares River. The soils are located in the supra- and meso-Mediterranean, dry and subhumid bioclimatic areas. Some now have vegetation of Quercus rotundifolia Lam. and Quercus pyrenaicae Willd. in serial stages, while others are used for cereal crops. The most indicative morphological variables of the eluviation process and their interrelationship with laboratory variables were studied (microstructure, texture, porosity, organic matter, and soluble salts). The E horizons have a loss of micromass in the thin section that coincides with a reduction in chlorides, sulfates, and electrical conductivity of the extract, as well as a very low ratio of Ca/Al water-soluble elements. Leaching is occasionally not shown in the granulometric analyses, but the transfer of matter due to biological activity and/or soil management is observed in the thin soil section. The Na+/Ca ratio greater than or equal to 1 matches a less stable microstructure, with a predominance of planar voids over vughs and channels. Sail use must be considered in the interpretation of this ratio. The eluviation horizons not described morphologically as such, namely Ap, Au, and Bw horizons in the rana formations and Au2, AB, and Bt1 horizons on the terrace, are always located in the upper 40 cm of soils that are used by plants. These are distinguished from the E horizons in their greater retention of available water and, depending on the eluviation intensity, a macroporosity higher than textural porosity.
Author

Seasonal water potential changes and proline accumulation in Mediterranean shrubland species (Plant Ecology, 1994)
We studied the water relations of 6 shrub and 3 tree species typical of the mediterranean climate region of central Spain to identify differential responses to water stress between and within species, and to determine if free proline concentration in leaves could be used as a water stress indicator. Predawn and midday water potentials (ffdw) on a seasonal basis, relative water content (RWC), leaf mass per area, foliar nitrogen and free proline concentrations were measured. The lowest water potentials were observed at the end of the summer, with recovery to higher water potentials in the fall and winter seasons. Species differed regarding the annual qdw fluctuation. Thymus zygis, Halimium viscosum, Genista hirsuta and Juniperus oxycedrus exhibited the most negative midday and predawn ~ w (both less than -6 MPa) with a large magnitude of response to changing conditions in soil moisture of the upper horizon of the soil. Lavandula pedunculata and Cistus ladanifer showed a moderate response. Quercus rotundifolia, Quercus faginea and Retama sphaerocarpa showed a modest response. The ~ w of different size individuals of Quercus rotundifolia and Cistus ladanifer were compared. The annual fflw fluctuation was greater in small individuals as compared to large individuals. In every species, there was an increase in proline concentration of bulk leaf tissues when predawn kVw dropped below -5 MPa. Small plants of Cistus ladanifer reached lower water potentials and also higher concentration of proline than bigger plants. Proline could possibly be used as a drought stress indicator in every species except Q. rotundifolia. It is suggested that in addition to water stress avoidance due to deep root systems, some mechanisms of water stress tolerance may operate among shrub and tree species of central Spain.